Analisis Kausalitas Penerimaan Pajak, Pengeluaran Pemerintah, dan Pertumbuhan Ekonomi di Indonesia - Ibrahim Wira Sanjaya; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
This study aims to analyze the causality between tax revenue, government expenditure, and economic growth in Indonesia . This type of study is descriptive and associative. This study uses time series data  from 1980 until 2019. This study uses the Vector Error Correction Model (VECM) method, Johansen Cointegration Test, and Granger Causality Test with tax revenue, government expenditure, and economic growth as independent variables. The results of this study indicate that: (1) There is causality between the tax revenue  variable and the government expenditure variable; (2) there is a one-way causality from the economic growth variable to the government expenditure variable; (3) there is a one-way causality from the economic growth variable to the tax revenue variable.